Synthesis of S- and N,S-Heterocycle–Dipeptide Conjugates for Supramolecular Hydrogel Formation - Ana-Morgana G. P. Silva; Maria F. Martins; Carlos B. P. Oliveira; José A. Martins; Paula M. T. Ferreira; Maria-João R. P. Queiroz (Molecules)
Small peptides with aromatic nuclei at the N-terminus have been shown to form bioactive, biocompatible, and biodegradable supramolecular peptide hydrogels. Novel heterocycle–dipeptide conjugates with potential biological activity or application as drug carriers were synthesized by using S-(benzo[b]thiophene) and N,S-(thieno [2,3-b]pyridine and thieno[2,3-b]quinoline) heterocycles as N-protective groups for dipeptides l-Phe-l-Phe and l-Phe-l-Leu. The synthesis involved coupling heterocyclic carboxylic acids with trifluoroacetate salts of ethyl l-phenylalanyl-l-phenylalaninate and ethyl l-phenylalanyl- l-leucinate using HBTU and Et3N, producing the corresponding six N-heterocycle–dipeptide ester conjugates, which were then hydrolyzed to the carboxylic acids. These conjugates were subjected to gelation tests in water starting from 0.4 wt% concentration of the conjugates, using a pH-lowering method with GdL. Among them, only the conjugate of benzo[b]thiophene with l-Phe-l-Phe-OH formed a hydrogel, with a gelation critical concentration of 0.15 wt% (GdL 0.6%) and a final pH of 6.8, which is important for biological applications. The hydrogel was characterized by STEM, revealing nanofibers with an average thickness of 17 nm that assemble into a 3D network capable of trapping water. Further rheological analysis demonstrated its viscoelastic behavior (G′ = 3.03 × 103 Pa; G″ = 3.28 × 102 Pa), comparable to the extracellular matrix of certain human tissues, crucial for biomedical applications.